Effect of silver nanoparticles on human mesenchymal stem cell differentiation - Sengstock, Christina; Diendorf, Jörg; Epple, Matthias; Schildhauer, Thomas A.; Köller, Manfred (Beilstein Journal of Nanotechnology, 2014)
Background: Silver nanoparticles (Ag-NP) are one of the fastest growing products in nano-medicine due to their enhanced antibacterial activity at the nanoscale level. In biomedicine, hundreds of products have been coated with Ag-NP. For example, various medical devices include silver, such as surgical instruments, bone implants and wound dressings. After the degradation of these materials, or depending on the coating technique, silver in nanoparticle or ion form can be released and may come into close contact with tissues and cells. Despite incorporation of Ag-NP as an antibacterial agent in different products, the toxicological and biological effects of silver in the human body after long-term and low-concentration exposure are not well understood. In the current study, we investigated the effects of both ionic and nanoparticulate silver on the differentiation of human mesenchymal stem cells (hMSCs) into adipogenic, osteogenic and chondrogenic lineages and on the secretion of the respective differentiation markers adiponectin, osteocalcin and aggrecan.Results: As shown through laser scanning microscopy, Ag-NP with a size of 80 nm (hydrodynamic diameter) were taken up into hMSCs as nanoparticulate material. After 24 h of incubation, these Ag-NP were mainly found in the endo-lysosomal cell compartment as agglomerated material. Cytotoxicity was observed for differentiated or undifferentiated hMSCs treated with high silver concentrations (≥20 µg·mL−1 Ag-NP; ≥1.5 µg·mL−1 Ag+ ions) but not with low-concentration treatments (≤10 µg·mL−1 Ag-NP; ≤1.0 µg·mL−1 Ag+ ions). Subtoxic concentrations of Ag-NP and Ag+ ions impaired the adipogenic and osteogenic differentiation of hMSCs in a concentration-dependent manner, whereas chondrogenic differentiation was unaffected after 21 d of incubation. In contrast to aggrecan, the inhibitory effect of adipogenic and osteogenic differentiation was confirmed by a decrease in the secretion of specific biomarkers, including adiponectin (adipocytes) and osteocalcin (osteoblasts).Conclusion: Aside from the well-studied antibacterial effect of silver, little is known about the influence of nano-silver on cell differentiation processes. Our results demonstrate that ionic or nanoparticulate silver attenuates the adipogenic and osteogenic differentiation of hMSCs even at non-toxic concentrations. Therefore, more studies are needed to investigate the effects of silver species on cells at low concentrations during long-term treatment.
Keywords: differentiation; differentiation marker; mesenchymal stem cells; nanoparticles; silver